A SOCIOLINGUISTIC STUDY OF ENGLISH AND JAVANESE KINSHIP TERMINOLOGY - Andrias Yulianto (Bandar Lampung University (UBL), 2016)
Misunderstanding in an interaction between people is commonly happened. One cause of this case is a different culture including the way to use language. This study intends to solve this problem by looking at one study in sociolinguistics focusing on the diversity of applying vocabulary in a kinship system of two different background societies, they are English and Javanese. The data collected from three sides, they are: the researcher's knowledge, available book, and participants. The study focuses on the native speaker of English and Javanese. This study results the differences and similarities taken from principles used in deciding kinship system (Nanda and Warms: 2007). Javanese has five priciples, they are Generation, Relative Age, Lineality and Collaterality, Gender, and Consanguineal and Affinal and English had four principles, they were Generation, Lineality and Collaterality, Gender, Consanguineal and Affinal.